2015
DOI: 10.1128/jcm.02980-14
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Rapid Point-of-Care (POC) Tests for Detection of Hepatitis B Surface Antigen in Field and Laboratory Settings in the Gambia, Western Africa

Abstract: f Hepatitis B virus (HBV) infection is a leading cause of death in sub-Saharan Africa (SSA). Point-of-care tests for hepatitis B surface antigen (HBsAg) could be an ideal tool for a large-scale HBV screening/treatment program in SSA. Using data from the PROLIFICA (Prevention of Liver Fibrosis and Cancer in Africa) program, we conducted a cross-sectional study to assess the diagnostic accuracy of three point-of-care tests (Determine, Vikia, and Espline) for the detection of HBsAg in the field or a laboratory se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 28 publications
3
86
2
1
Order By: Relevance
“…The rate of HBsAg loss (12.1%) we observed was higher than what has been listed in many reports from HIV-HBV-coinfected and CHB patients in high-income countries [32][33][34] but similar to the 17.6% reported by Hamers et al [29] and lower than the 36% observed by Anderson et al [35]. Our rate of HBsAg loss may be slightly overestimated due to our use of a rapid test on whole blood that has lower sensitivity than serum assays [36].…”
Section: Discussioncontrasting
confidence: 54%
“…The rate of HBsAg loss (12.1%) we observed was higher than what has been listed in many reports from HIV-HBV-coinfected and CHB patients in high-income countries [32][33][34] but similar to the 17.6% reported by Hamers et al [29] and lower than the 36% observed by Anderson et al [35]. Our rate of HBsAg loss may be slightly overestimated due to our use of a rapid test on whole blood that has lower sensitivity than serum assays [36].…”
Section: Discussioncontrasting
confidence: 54%
“…HBsAg was detected by radioimmunoassay (Ausria-I, Abbott, USA) in 1974,12 reverse passive haemagglutination assay (Wellcotest, Wellcome Diagnostics, UK) in 1980–1998,15 immunochromatography (Determine, Abbott) in 2003–2008,20 and chemiluminescent microparticle immunoassay (Architect, Abbott) in 2012–2013 21. HBsAg-positive samples were tested for HBeAg by radioimmunoassay in 1980–199815 and later by enzyme immunoassay (EIA) (Diasorin, Biomedica, Italy) 20.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in addition to the fact that the NBTP recommends the use of a single rapid diagnostic test (RDT) to assess the risk of HBV infection, Determine HBsAg tests are recognized to be less sensitive in some studies [53] [54] [55]. The ELISA chain can be considered as an alternative for confirmation of the results [25] [26] [34].…”
Section: From the Methods Of Screening And Diagnosis Of Hbv Infection:mentioning
confidence: 99%